Handbook of pediatric orthopaedics - Sponseller, Paul D. (Thieme, 2020)
"This compact handbook is a succinct, how-to manual covering a diverse spectrum of pediatric orthopaedic procedures. The book is organized by nine chapters, six of which are dedicated to specific disorder categories. An introductory chapter on anatomy and normal childhood development features norms for osseous and motor development, innervation, growth patterns, predictions, and new guidelines for assessing growth at the pelvis, foot, and hand. Expanded content on skeletal growth, development, and systemic disorders and skeletal syndromes reflects the latest knowledge, such as imaging parameters, clinical treatment standards, and an algorithm for DDH treatment. Cutting-edge advances in the treatment of cerebral palsy, myelodsplasia, and spinal muscular atrophy are detailed in the chapter dedicated to neuromuscular disorders. Pediatric trauma content includes important updates on forearm and femur fractures, an outlined approach to each fracture, and a diagram showing how to reduce each type of Monteggia fracture"--Publisher's description